2018
DOI: 10.1097/brs.0000000000002697
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Utility of the Hoffmann Sign for the Diagnosis of Degenerative Cervical Myelopathy

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The Hoffman sign has a prevalence of 2% in the general population, although a positive predictive value of 68% and negative predictive value of 70% for CSM make it a useful adjunct in diagnosis. 33,34 Sensory changes due to compression of the spinothalamic tract, posterior column, and spinal roots can lead to changes in pain, temperature, proprioception, and general dermatomal sensation. 7 Specific sensory findings in the upper extremity and thorax in patients with CSM include neck pain (50%), radicular pain (38%), and a positive Lhermitte sign (27%).…”
Section: Upper Extremity Findingsmentioning
confidence: 99%
“…The Hoffman sign has a prevalence of 2% in the general population, although a positive predictive value of 68% and negative predictive value of 70% for CSM make it a useful adjunct in diagnosis. 33,34 Sensory changes due to compression of the spinothalamic tract, posterior column, and spinal roots can lead to changes in pain, temperature, proprioception, and general dermatomal sensation. 7 Specific sensory findings in the upper extremity and thorax in patients with CSM include neck pain (50%), radicular pain (38%), and a positive Lhermitte sign (27%).…”
Section: Upper Extremity Findingsmentioning
confidence: 99%
“…Database records containing ‘Degenerative Cervical Myelopathy’ in their title were searched and the results were filtered using the medline filter by publication type: systematic review. The results were sorted by year of publication and the top three systematic reviews that were not co‐authored by any of the co‐authors in this study were chosen for filter validation (Fogarty et al, 2018; Tetreault et al, 2016; Wang et al, 2019). A total of seventy‐seven references were identified from the systematic reviews, and their full texts were analysed to confirm eligibility.…”
Section: Methodsmentioning
confidence: 99%
“…There are a few recent studies that have looked at the validity of upper extremity reflexes and Hoffman sign. In a systematic review of 201 patients presenting to spine specialists from three separate cross-sectional studies, Fogarty et al [24] reported the positive likelihood ratio (ie, likelihood that a patient with cervical myelopathy will test positive) of a positive Hoffman's sign for cervical myelopathy to range between 1.8 -6.0 with a combined value of 2.6 (95% CI 1.8-3.9) and a negative predictive value (ie, probability that a patient with a negative test does not have cervical myelopathy) of 70%. This represents only a modest contribution to the overall diagnostic picture of a patient with degenerative cervical myelopathy.…”
Section: Case For Cervical Spine Clearancementioning
confidence: 99%